An Exact Solution of the 2D Boussinesq Equation for the Three‐Point Method. Issue 4 (9th May 2019) - Szymański, Adam
Abstract : Article impact statement : The closed‐form solution of the steady‐state 2D Boussinesq equation better approximates the water table than the three‐point method, when information is available on the recharge, the hydraulic conductivity and the base of the aquifer.